Assessing the adoption and use of integrated library systems (ILS) for library service provision in academic libraries in Edo and Delta states, Nigeria. Issue 8 (7th November 2016) - Omeluzor, Saturday U.; Oyovwe-Tinuoye, Gloria O.
Abstract : Purpose: The purpose of this study is to investigate the use of integrated library system (ILS) in academic library operations in Edo and Delta states, Nigeria. Design/methodology/approach: This study adopted a descriptive survey research design. Total enumeration was used since the population consisting 88 academic librarians in Edo and Delta states is not large and was considered appropriate to achieve the purpose of this study. Questionnaire titled "Assessment of adoption and use of Integrated Library Software (ILS) for library service provision in academic libraries in Edo and Delta States, Nigeria" was used. Before the administration of the questionnaire on the respondents, face validity was carried out to test the validity of the questions. The questionnaire was given to experts in the Department of Information Resources Management, Babcock University, Ilishan-Remo, Ogun State who validated, resolved defects and modified the questionnaire. Findings: This study showed that there is a general non-use of ILS in academic libraries in Delta state. Findings revealed that three of the four academic libraries in Edo State adopted library software in their library operations except Ambrose Ali University Library, Ekpoma. Findings further showed that the ILS that were used in academic libraries in Edo State are effective. It also revealed that ILS is effective for accessing books and other library materials, retrieval of materials, bibliographic search and provision of links to external databases. Finding also indicated that among the library software that were used in academic libraries in this study, only Koha ILS has the capacity to link to external databases. Practical implications: The use of ILS in academic library operation is critical. Its adoption and use to a large extent positively affect the library and its users. Non-adoption and use of ILS in most academic libraries is a setback to delivery of quality library services to clientele. Originality/value: This study is the first that assessed the adoption and use of ILS in academic libraries is Edo and Delta states. It exposed the level of adoption and utilization of ILS in library operations with a view to encouraging libraries to adopt and use ILS for library services.